DFT study of H 2 adsorption on Pd-decorated single walled carbon nanotubes with C- vacancies - López Corral, Ignacio (2012)
Carbon nanotubes are considered important materials for hydrogen storage. Although theCeH interaction is very weak at room temperature, the incorporation of highly dispersedPd nanoparticles increases the H2 adsorption on carbon surfaces. In this work we performeddensity functional theory studies of H2 adsorption on single walled carbon nanotubes(SWCNTs) with C-vacancies and a Pd decoration. We used the VASP and SIESTAcodes. Our calculations show that Pd adsorption is favored on the C-vacancies of the (5,5)SWCNT, while H2 adsorption also occurs preferentially on C-defective sites.